Pengaruh Literasi Manajemen Keuangan dan Perilaku Kewirausahaan Pemilik Usaha Terhadap Kinerja UMKM Bidang Kuliner di Indralaya - Puspita, Reni Ayu; Andriana, Isni; Isnurhadi, Isnurhadi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of financial management literacy and entrepreneurial behavior of business owners on the performance of MSMEs in the culinary field in Indralaya. The population in this study amounted to 74 SMEs using a purposive sampling technique. The data collection technique used was a questionnaire. The data analysis technique used is multiple linear regression analysis. The data was processed using the Satisficial for product and service solution (SPSS) program version 26. The results showed that financial management literacy and entrepreneurial behavior had a significant effect on the performance of MSMEs in the culinary sector in Indralaya. Keywords: Financial Management Literacy, Entrepreneurial Behavior, MSME’s Performance